Islamic educational values in the interpretation of surah al-‘alaq verses 1-5 and their relevance to the merdeka curriculum - Asd’a Amatullah; Ahmad Nurrohim; Widiyanto; Namer Alotaibi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine the values of Islamic education found in Surah Al-‘Alaq verses 1–5 and their relevance to the implementation of the Merdeka Curriculum in Indonesia. Using a qualitative approach with thematic interpretation (tafsir maudhu’i) and contextual analysis, this study explores three core educational values presented in the first revelation of the Qur’an: (1) spiritual education (faith and worship), (2) moral and psychosocial education (ethics and self-development), and (3) intellectual and scientific education (literacy and scientific exploration). The findings indicate that these values align with the six dimensions of the Pancasila Student Profile, particularly in shaping students to be faithful, critical thinkers, creative, and globally-minded. Integrating the values of Al-‘Alaq into the Merdeka Curriculum can be realized through project-based learning that connects Qur'anic literacy with science, habituation of noble character, and reinforcement of 21st-century competencies. These findings affirm that a holistic Islamic educational approach is not only compatible with the vision of national education but also offers solutions to contemporary challenges such as moral decline and the fragmentation of knowledge in the modern era.Keywords: Islamic Education, Surah Al-Alaq, Merdeka Curriculum, Tafsir Tarbawi, Pancasila Student Profile